CD28− Cells Are Increased in Early Rheumatoid Arthritis and Are Linked With Cytomegalovirus Status - Thompson, Charlotte; Davies, Ruth; Williams, Anwen; Jones, Gareth; Choy, Ernest H. S. (Frontiers in Medicine, 2020)
Objective CD3+CD8+CD28- cells are higher in Rheumatoid Arthritis (RA). The aim of this study was to assess CD3+CD8+CD28- cells in patients with early RA and assess the effects of cytomegalovirus (CMV) seropositivity. Method In this prospective observation study, fifty RA patients were recruited from Cardiff University Hospital of Wales (UHW) rheumatology outpatient, 25 patients with early disease (disease duration 0-6 months) and 25 patients with established disease (>2 years). Clinical and serological markers of inflammation were noted, and peripheral blood mononuclear cells were analysed using flow cytometry. Results The percentage of the CD3+CD8+CD28- T cells was increased in early RA patients and was associated with disease duration. The percentage of CD3+CD8+CD28- T cells was increased in CMV positive early and established RA grouped and early RA patients in comparison to CMV negative patients (p<0.05). There is a weak but statistically significant correlation between the percentage of CD3+CD8+CD28- cells and CRP in CMV positive RA patients (r=0.227, p<0.05). Conclusion The percentage of CD3+CD8+CD28- cells is higher in early RA patients and correlates with disease duration, highlighting a potential role early in the disease process. These cells were also higher in CMV positive early RA patients which may suggest a role of CMV in disease development.